Mood Disorders and Psychotherapeutics Team-Based Learning Activity - Dawnelle Schatte; Ruth Levine; Melissa Allen; Chase Findley (Association of American Medical Colleges, 2016)
Abstract Introduction Following the publication of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), this module was created by a collaborative of psychiatric educators in the University of Texas System for the Revised DSM-5 Psychiatry Clerkship Common Curriculum. To pool our resources and introduce innovation, our group of four medical schools (spread across five sites) decided to develop, peer-review, introduce, and study one curriculum. Methods This resource specifically covers both mood disorders and the basic classes of psychopharmacology and psychotherapy and was used for third-year medical students as part of their required psychiatry clerkship. Learning involves preclass reading preparation, in-class readiness assurance exercises, and application activities. Students are graded on both group and individual performance. Results After administration, formal end-of-course evaluations concerning team-based learning (TBL) were positive, with students agreeing or strongly agreeing with the statement "TBL increased my understanding of course material" at a rate of 79%-95%. Discussion We believe that the multischool collaboration and peer review of this module have created a better quality resource than any of the schools would have been able to develop individually. The module adds to the choices of quality materials available for educators to use when designing their curricula, and the collaboration can serve as a model for other such endeavors.